Notes on the Genus Aceratoneuromyia Girault (Hymenoptera: Eulophidae) - Ning Huangfu; Huan-Xi Cao; Chao-Dong Zhu (Insects, 2022)
Fruit flies in the family Tephritidae are well known as economically important pests of edible fruits and can often cause serious damage and losses to both agriculture and the economy. One of the common parasitoids of fruit flies, Aceratoneuromyia indica (Silvestri), has been used in biological programs. However, the biocontrol utilities of parasitoids are impeded by the difficulties of proper identification. Species of the genus Aceratoneuromyia Girault (Hymenoptera: Eulophidae), usually developed as parasitoids of fruit flies, are studied here. Trjapitzinichus Kostjukov and Kosheleva is proposed as a new synonym under Aceratoneuromyia. Three new species of Aceratoneuromyia, A. bilinis Huangfu and Cao sp. nov., A. carinata Cao and Zhu sp. nov., and A. trilinus Cao and Zhu sp. nov., are described and illustrated from China. Aceratoneuromyia indica is also treated here with diagnosis and illustrations. DNA barcodes of A. bilinis and A. indica and a key to the world species of Aceratoneuromyia are provided. This study provided important identification information of parasitoids with morphology and molecular evidence, which is useful for imperative needs regarding the identity of parasitoids attacking fruit flies.